Prophylactic Anti-Osteoporotic Effect of Matricaria chamomilla L. Flower Using Steroid-Induced Osteoporosis in Rat Model and Molecular Modelling Approaches - Abirami Raja; Govind Pratap Singh; Sana A. Fadil; Sameh S. Elhady; Fadia S. Youssef; Mohamed L. Ashour (MDPI AG, 2022)
The anti-osteoporotic activity of ethanol extract from the Matricaria chamomilla L. flower was evaluated using steroid-induced osteoporosis in a rat model for the first time. Biochemical parameters such as serum calcium, phosphate, magnesium, creatinine, and alkaline phosphatase were assessed. At a 400 mg/kg body weight dose, the extract showed 54.01% and 27.73% reduction in serum calcium and phosphate ions serum levels, respectively. Meanwhile, it showed a 20% elevation in serum magnesium level, compared to the steroid-treated group. It also showed a significant decrease in creatinine and alkaline phosphatase levels, by 29.41% and 27.83%, respectively. The obtained results were further supported by biomechanical analyses, which revealed that a 400 mg/kg body weight dose of the flower extract increased bone strength and thickness. At the same time, it does not affect the bone length, compared to the diseased group. Histopathological examination revealed that the extract showed a significant increase in trabecular thickness, and it had restored the architecture of the cortical and trabecular structure with well-organized bone matrix. The possible inhibitory effect of the major phenolic compounds identified from the plant extract on cathepsin K was investigated using molecular docking. Rutin (4) had the best-fitting score within the active site, as evidenced by the free binding energy, (∆G = −54.19 Kcal/mol). ADMET/TOPKAT revealed that the examined compounds had variable pharmacodynamics and pharmacokinetic properties that could be improved to enhance the bioavailability during incorporation in various dosage forms. Thus, it can be concluded that this plant extract showed potential therapeutic benefits for osteoporosis.